2021
DOI: 10.1111/cas.14970
|View full text |Cite
|
Sign up to set email alerts
|

Ral GTPase–activating protein regulates the malignancy of pancreatic ductal adenocarcinoma

Abstract: The small GTPases RalA and RalB are members of the Ras family and activated downstream of Ras. Ral proteins are found in GTP‐bound active and GDP‐bound inactive forms. The activation process is executed by guanine nucleotide exchange factors, while inactivation is mediated by GTPase‐activating proteins (GAPs). RalGAPs are complexes that consist of a catalytic α1 or α2 subunit together with a common β subunit. Several reports implicate the importance of Ral in pancreatic ductal adenocarcinoma (PDAC). However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…We used biochemical assays to confirm that MP2_HDAC1_OE cells have higher GTPase activity than control cells and that cells treated with a HDACi have further reduced GTPase activity. GTPase signaling is involved in pancreatic cancer initiation, metastasis, and drug resistance 46 . Increased GTPase signaling leads to the activation of key pathways, such as MAPK and PI3K, that regulate cell proliferation, migration, and survival in cancer 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used biochemical assays to confirm that MP2_HDAC1_OE cells have higher GTPase activity than control cells and that cells treated with a HDACi have further reduced GTPase activity. GTPase signaling is involved in pancreatic cancer initiation, metastasis, and drug resistance 46 . Increased GTPase signaling leads to the activation of key pathways, such as MAPK and PI3K, that regulate cell proliferation, migration, and survival in cancer 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Throughout this study, our gene set enrichment analyses of genes associated with HDAC1 overexpression consistently revealed GTPase activity as an enriched process. A variety of proteins contribute to GTPase activity and many are druggable 47 , which makes them of potential clinical interest. We have shown that expression of GTPases and GTPase activating proteins are associated with worse overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most tissues express both α subunits, with α1 predominant in the brain and α2 in the liver and lung ( 8 ). In the pancreas, the expression levels of α1 and α2 subunits are similar ( 9 ).…”
mentioning
confidence: 99%
“…In pancreatic cancer, Ral has been shown to be highly activated in cancer tissues with K-Ras mutations ( 18 ). We have previously generated RalGAPβ-deficient PDAC cells using two cell lines, MIA PaCa-2 and PANC-1, and found that these cells have high Ral activity and exhibit high invasive and metastatic capacities ( 9 ). However, since Ral can interact with various downstream effectors such as the exocyst complex, RalBP1, phospholipase D, and M-Sec, it remains unclear how Ral regulates invasion and metastasis of PDAC cells.…”
mentioning
confidence: 99%